“You broke up with me - I am just going to smoke again!” Smoking Cessation Relapse Triggers - Lamonica, Aukje (International Journal of Qualitative Methods, 2012)
tex.unique-id: ISI:000323937100300
Keywords: dept.pch; ⛔ No DOI found

Risk behaviors among suburban women who use methamphetamine: social harms and social solutions - Lamonica, Aukje K; Boeri, Miriam W (Journal of Applied Social Science, 2015)
We propose that female methamphetamine users who live in suburbia experience risks for disease transmission stemming from their social environment that remain under the radar of public health surveillance networks. The data analyzed in this article were collected from 2007 to 2011 and were drawn from two sequential studies on methamphetamine use. The studies were conducted in the suburbs of a southeastern U.S. metropolis. We analyzed a total of 65 qualitative interviews with former and active methamphetamine-using women. Data from focus groups also were included in the analysis. The participants’ ages ranged from 18 to 51 years. We identified three major themes with regard to risk behaviors and transmission of infectious diseases: (1) setting risk behaviors such as sharing syringes and homelessness, lack of transportation, and unemployment; (2) sexual risk behaviors such as condom use and having multiple partners; and (3) service-related risks such as risk awareness and prevention behaviors as well as utilization of social services and health care. Our findings point to the pervasive nature of social influences on the risk for infectious disease transmission. We suggest that harm-reduction programs (HRPs) be implemented in suburban communities to increase access to these services. Second, our data support the concept of social recovery for drug users to better their health and social lives holistically. © 2014, © The Author(s) 2014.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/111-463-430-841-658 tex.type: [object Object]
Keywords: addiction; dept.pch; drugs; environment; qual-heavy

Naloxone perspectives from people who use opioids: Findings from an ethnographic study in three states. - Boeri, Miriam W.; Lamonica, Aukje K. (Journal of the American Association of Nurse Practitioners, 2020)
BACKGROUND: Naloxone is an opioid antagonist that can reverse an opioid overdose. Increased opioid-related mortality rates led to greater distribution of naloxone without a prescription and administration of naloxone by laypersons. This study fills a gap in knowledge of naloxone experiences among active users of opioids living in suburban communities. PURPOSE: The purpose of this article is to provide nurse practitioners with an in-depth understanding of current naloxone use practices among people who experience overdose events. The specific aims are to compare access to naloxone in diverse suburban towns, to examine administration differences across settings, and to understand perspectives on naloxone experiences from people who are actively using opioids. METHODOLOGICAL ORIENTATION: The data for this analysis were drawn from an ethnographic study in the suburban towns around Atlanta, Georgia; Boston, Massachusetts; and New Haven, Connecticut. Short surveys and in-depth interviews were collected. Inductive methods were used to compare data across settings. SAMPLE: The sample of 106 included 48% female, 62% White, 24% African American/Black, 13% more than one race, and 21% Hispanic/Latinx. The mean age was 41.35 years. CONCLUSIONS: Differences between study settings in access to naloxone, administration frequency, and delivery systems were found. Findings suggest more education and training is needed in overdose prevention and harm reduction intervention. Studies on delivery systems need to address the increase in fentanyl-related overdoses. IMPLICATIONS FOR PRACTICE: Nurse practitioners can help to target distribution of naloxone in local communities, facilitate collaboration with harm reduction services, and provide evidence-based education and training to laypersons. Copyright © 2020 American Association of Nurse Practitioners.
6 citations (Crossref) [2023-10-31]
Keywords: Adult; Analgesics; Opioid; Drug Overdose; Female; Harm Reduction; Humans; Male; Naloxone; Narcotic Antagonists; adult; dept.pch; drug overdose; female; harm reduction; human; male; naloxone; narcotic analgesic agent; narcotic antagonist; peer-reviewed

Mothers who use opioids and are involved in the criminal justice system: A transformative justice approach - Boeri, Miriam; Lamonica, Aukje; Smith, Sierra (Human Organization, 2025)
Keywords: Criminal justice; Criminology; Developmental psychology; Economic Justice; Law; Political science; Psychology; Restorative justice; Sociology; Theory of criminal justice; Transformative learning; dept.pch; mothers; opioids; recovery; relapse

The impact of social isolation policies during COVID-19 on suburban mothers and pregnant women with opioid use disorder - Lamonica, Aukje; Boeri, Miriam; Khan, Mishal (Women & Health, 2024)
The aim of this qualitative research paper was to identify how social isolation policies implemented during the COVID-19 pandemic impacted the lives of pregnant women and mothers with opioid use disorder. Between 2020 and 2022, in-depth interviews were conducted with 37 mothers and pregnant women living in the suburbs of Newark, NJ, and New Haven, CT. Participants had to be at least 18 years old, misused or abused opioids in the last 12 months while residing in a suburban location, and pregnant or caring for children aged 12 and younger. We used syndemics theory to guide our grounded theory analysis to identify relationships between social situations, health conditions, and opioid use disorder. Five major themes emerged that were either directly or indirectly impacted by social isolation caused by policies implemented during the COVID-19 pandemic: Relationships, Environment, Services, Drug Use, and Health. Findings from this study reveal new insights into how mothers and their health were impacted by prolonged social isolation policies and offer suggestions for policymakers and service providers to better address future crisis.
_eprint: https://doi.org/10.1080/03630242.2024.2377640
Keywords: COVID-19; dept.pch; mothers; opioid use disorder; peer-reviewed; social isolation policy

Gaps in medical marijuana policy implementation: Real-time perspectives from marijuana dispensary entrepreneurs, health care professionals and medical marijuana patients - Lamonica, Aukje K.; Boeri, Miriam; Anderson, Timothy (Drugs: Education, Prevention and Policy, 2016)
Aims: There is a need for greater understanding of the recursive processes involved in drug policy development and its impact on stakeholders. The aim of this study was to examine the challenges of implementing marijuana policy in Massachusetts, where recent policy shifts have occurred. Methods: Qualitative data were generated from ethnographic field notes, media reports, public records and in-depth interviews with 25 stakeholders, including six medical marijuana dispensary entrepreneurs, eight health care professionals and 11 medical marijuana patients. Data were triangulated using a grounded theory approach. Findings: Stakeholders expressed confusion and misunderstanding, and demonstrated that they held conflicting interpretations of the policy and regulations. Analyses revealed gaps in policy development and implementation that are organised by three specific core implementation processes and the themes of transparency, communication and education. Conclusions: Findings show a need for more transparency in implementation processes, a more effective mode of communicating regulations, and a comprehensive plan for medical marijuana education. Based on our findings, we provide recommendations to help policymakers in the US and other countries considering legalisation of marijuana or other drugs.
12 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/082-965-046-127-943 tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.researcherid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Cannabis; dept.pch; drug education; education; ethnography; health care provider; policy; public health; qualitative research

Circumstances of overdose among suburban women who use opioids: Extending an urban analysis informed by drug, set, and setting. - Lamonica, Aukje K; Boeri, Miriam; Turner, Jeffrey (The International journal on drug policy, 2021)
BACKGROUND: Opioid overdoses are primarily discussed by the pharmacological properties of the drugs used. Research shows that other factors such as the social/physical environment and the mental/emotional states can have an impact on overdose events. Ataiants and colleagues (2020) used Zinberg's "drug, set, and setting" framework to identify circumstances surrounding overdose experiences of street-involved women in Philadelphia. The aim of this paper is to extend their analysis to a diverse sample of suburban women who experienced overdoses., METHODS: The mixed-methods design consisted of ethnographic fieldwork, in-depth interviews, and brief surveys with 32 suburban women who use opioids. Inductive theoretical reasoning and constant comparative analysis facilitated themes emerging within the "drug, set, and setting" framework., RESULTS: Eighteen out of 32 women identified "drug" as the primary factor involved in their overdose events. Major themes were an inability to identify the synthetic opioid fentanyl, lack of knowledge or control over how much to use, poly-substance use, and an insufficient understanding of risks. Eleven out of 32 women linked "set" to their overdose experiences. Themes included emotional trauma, such as death of a child, child custody issues, and mental health conditions, such as depression. Six out of 32 women associated "setting" with one of their overdose experiences. Themes were related to being with friends or partners that used, and having recently been released from treatment or incarceration., CONCLUSION: Findings show similar themes found among an urban sample, adding insight on the need for effective overdose interventions targeted for suburban populations. The opioid crisis is not confined to the cities, and neither should services aimed at addressing opioid overdose. The knowledge provided here can help policy makers support female-centered harm reduction services not only in urban areas but also in the suburbs. Copyright © 2020. Published by Elsevier B.V.
9 citations (Crossref) [2023-10-31] Place: Netherlands Lamonica, Aukje K. Southern Connecticut State University, 501 Crescent Street, New Haven, CT 06515, United States. Electronic address: lamonicaa1@southernct.edu. Boeri, Miriam. Bentley University, 175 Forest Street, Waltham, MA 02452, United States. Turner, Jeffrey. Southern Connecticut State University, 501 Crescent Street, New Haven, CT 06515, United States.
Keywords: *Drug Overdose; *Pharmaceutical Preparations; Analgesics; Analgesics; Opioid/tu [Therapeutic Use]; Article; Child; Drug Overdose; Drug Overdose/dt [Drug Therapy]; Drug Overdose/ep [Epidemiology]; Female; Fentanyl; Humans; Opioid; Pennsylvania; Pharmaceutical Preparations; Philadelphia; adult; child; child custody; childhood mortality; controlled study; depression; dept.pch; drug; drug overdose; ethnography; female; fentanyl; human; incarceration; inductive reasoning; interview; major clinical study; mental health; narcotic analgesic agent; opiate addiction; peer-reviewed; polypharmacy; priority journal; psychotrauma; risk factor; suburban area; urban area; women's health

Social justice with harm reduction approaches for mothers who use opioids: an international comparative ethnographic study with community engaged methods - Boeri, Miriam; Lamonica, Aukje; Whittaker, Anne; Bruce, Marisa (Harm Reduction Journal, 2025)
BACKGROUND: Mothers and pregnant women who use opioids are particularly vulnerable. Mothers often fear surveillance, stigma, and loss of custody of their children when seeking treatment. Although opioid agonist therapy (OAT) has been shown to be effective, access varies regionally, and not all mothers can cease using opioids. This study compares outcomes of mothers who use opioids in the UK with universal healthcare and OAT access, and mothers in the U.S. with restricted healthcare and OAT access, focusing on their interactions with services. METHODS: This is a secondary data analysis of two studies on mothers who use opioids. Data were collected from nine mothers in Scotland (UK) and 20 mothers in New Jersey (US) through ethnographic, longitudinal studies spanning one year. The UK study used a "Learning Alliance" engagement approach, a patient/public engagement model that involves stakeholders in developing objectives and the dissemination of findings. The US study engaged "community-based consultants," who are paid individuals with lived experience from the study field communities to assist researchers in recruitment and ethnographic fieldwork. Ethical approval was received from review boards. Data were anonymized before analysis, and people with lived experience provided feedback on findings. Grounded theory methods were used for analysis. RESULTS: Findings reveal both convergent and divergent experiences. Mothers in Scotland had more access to healthcare and social housing but faced increased surveillance, while New Jersey mothers often experienced housing insecurity and difficulty obtaining healthcare. Shared challenges included trust issues, stigmatization, inconsistent practitioner engagement, responsibilization, and unclear expectations from child protection services. While Scottish mothers had better access to OAT, both groups faced child custody loss due to unregulated drug use. Mothers in both studies were struggling to meet reunification requirements of abstinence (with or without OAT) within the required time frame. CONCLUSIONS: Differing governance structures create persistent challenges across national boundaries. While health practitioners generally support harm reduction strategies, it does not go beyond OAT for mothers. Our findings indicate the need for radical harm reduction approaches with social justice for mothers who use drugs, including safer parental drug use strategies.
Keywords: Child protection; Community engagement; Corporate governance; Criminal justice; Economic Justice; Ethnography; Harm; Harm reduction; Health psychology; Mothers who use drugs; Opioids; SAFER; Social policy; dept.pch

Language preferences and impact of labels on the lived experience of people who use heroin - Boeri, Miriam; Lamonica, Aukje K.; Chow, Clifton; Whalen, Thor (Drugs: Education, Prevention and Policy, 2023)
0 citations (Crossref) [2023-10-31] _eprint: https://doi.org/10.1080/09687637.2023.2262097
Keywords: Stigma; attitudes; dept.pch; heroin; labels; language preferences; lived experience; mixed methods; peer-reviewed; replication studies

Barriers and Motivators to Opioid Treatment Among Suburban Women Who Are Pregnant and Mothers in Caregiver Roles. - Boeri, Miriam; Lamonica, Aukje K; Turner, Jeffrey M; Parker, Amanda; Murphy, Grace; Boccone, Carly (Frontiers in psychology, 2021)
Women of childbearing age who misuse opioids are a particularly vulnerable population, and their barriers to treatment are unique because of their caregiver roles. Research on treatment for opioid use generally draws from urban and rural areas. This study fills a gap in research that focuses on barriers and motivators to opioid treatment in suburban areas. The aim of this study was to give voice to suburban pregnant women and mothers caring for children while using opioids. Ethnographic methods were used for recruitment, and 58 in-depth interviews were analyzed using a modified grounded theory approach. Barriers to medication-assisted treatment (MAT) included stigma, staff attitudes, and perceptions the women had about MAT treatment. Barriers associated with all types of treatment included structural factors and access difficulties. Relationships with partners, friends, family, and providers could be barriers as well as motivators, depending on the social context of the women's situation. Our findings suggest increasing treatment-seeking motivators for mothers and pregnant women by identifying lack of resources, more empathetic consideration of social environments, and implementing structural changes to overcome barriers. Findings provide a contemporary understanding of how suburban landscapes affect mothers' treatment-seeking for opioid dependence and suggest the need for more focus on emotional and structural resources rather than strict surveillance of women with opioid dependence who are pregnant or caring for children. Copyright © 2021 Boeri, Lamonica, Turner, Parker, Murphy and Boccone.
2 citations (Crossref) [2023-10-31] Place: Switzerland Boeri, Miriam. Department of Sociology, Bentley University, Waltham, MA, United States. Lamonica, Aukje K. Department of Public Health, Southern Connecticut State University, New Haven, CT, United States. Turner, Jeffrey M. Department of Public Health, Southern Connecticut State University, New Haven, CT, United States. Parker, Amanda. Department of Sociology, Bentley University, Waltham, MA, United States. Murphy, Grace. Department of Sociology, Bentley University, Waltham, MA, United States. Boccone, Carly. Department of Sociology, Bentley University, Waltham, MA, United States.
Keywords: dept.pch; peer-reviewed